2020
DOI: 10.1002/jlb.3covr0520-272r
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine storm and leukocyte changes in mild versus severe SARS-CoV-2 infection: Review of 3939 COVID-19 patients in China and emerging pathogenesis and therapy concepts

Abstract: Clinical evidence indicates that the fatal outcome observed with severe acute respiratory syndrome‐coronavirus‐2 infection often results from alveolar injury that impedes airway capacity and multi‐organ failure—both of which are associated with the hyperproduction of cytokines, also known as a cytokine storm or cytokine release syndrome. Clinical reports show that both mild and severe forms of disease result in changes in circulating leukocyte subsets and cytokine secretion, particularly IL‐6, IL‐1β, IL‐10, TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
635
2
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 664 publications
(686 citation statements)
references
References 191 publications
(213 reference statements)
23
635
2
26
Order By: Relevance
“…Comorbidities such as hypertension, diabetes, obesity, and atherosclerosis are related to the severe form of the disease, being more prevalent among hospitalized individuals with a higher average-case lethality [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. The disease severity is characterized by the overactivation of the immune system causing a cytokine storm responsible for cytokine release syndrome (CRS) [ 13 , 14 ]. The inflammatory response starts with a local release of cytokines, such as interleukin-6 (IL-6) and tumoral necrosis factor-alpha (TNF-α), that may spread systemically, leading to acute respiratory distress syndrome (ARDS) and multiple organ failure, the final result being death, at least in the most severe cases of COVID-19 [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidities such as hypertension, diabetes, obesity, and atherosclerosis are related to the severe form of the disease, being more prevalent among hospitalized individuals with a higher average-case lethality [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. The disease severity is characterized by the overactivation of the immune system causing a cytokine storm responsible for cytokine release syndrome (CRS) [ 13 , 14 ]. The inflammatory response starts with a local release of cytokines, such as interleukin-6 (IL-6) and tumoral necrosis factor-alpha (TNF-α), that may spread systemically, leading to acute respiratory distress syndrome (ARDS) and multiple organ failure, the final result being death, at least in the most severe cases of COVID-19 [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As JAK inhibitors attenuate JAK signaling and subsequent cytokine release, their administration may best be suited for patients with progressing COVID-19 who have not yet experienced a cytokine storm. [40] By contrast, as Type I interferons induce cellular antiviral states via the JAK/STAT pathway, its administration may be most efficacious early on in disease progression where the virus is still replicating. While the literature surrounding this is sparse, one study included in this meta-analysis concluded that early administration of interferon-alpha-2b could induce positive outcomes in COVID-19 patients compared to standard treatment, while its late administration was associated with slower recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have found two RBM-cross-reactive monoclonal antibodies that competitively and MCP-1). It has also been suggested as a "driver" of the disease progression particularly in a subset (~ 20%) of COVID-19 patients with more severe pneumonia that often escalates to respiratory failure and death [26][27][28][29] . Furthermore, GM-CSF might also be a key mediator of the cytokine storm in COVID-19 and other inflammatory diseases 30,31 .…”
Section: Discussionmentioning
confidence: 99%